A Rhetorical, Stylistic and Translation Quality Assessment Based -Study of English and French Translations of Al-Sayyab’s Poem (Lianni Ghareeb- For I’m Stranger - (لأني غريب - Ismail, Ismail (Al-Adab Journal, 2023)
Arabic Poetry in general and Iraqi Modern Poetry in particular are abundant in emotional, nationalistic and political attitudes. Iraqi poets express their devotion and loyalty to their homeland profoundly and figuratively. Badr Shaker Al-Sayyab is an Iraqi pioneering figure in modern Arabic poetry. His poem (For I’m Stranger) is one of his powerful and effective literary works in which he draws magnificent images of the strong psychological bond with his homeland Iraq. This poem is a challenging task for translators (from Arabic into any other language). So, this paper focuses on how to render the meter and the rhyme of the source Arabic poem which has unique stylistic and prosaic structures into the TL concerned? The study includes an analysis of the English and French versions of "Liaani Ghareeb لأني غريب" poem. The analysis is made by comparing musical, rhetorical and figurative structures of the two versions to see which version is closer to the Arabic SL poem. This study comes up with the conclusion that the metrical and prosodic structures of the French version are more harmonic in terms of musicality. The English version on the other hand seems acceptable but lacks the rhetorical compatibility in the light of the adopted theories of translation.